2012
DOI: 10.5380/rf.v42i1.26305
|View full text |Cite
|
Sign up to set email alerts
|

CARACTERIZAÇÃO E PATOGENICIDADE DE ISOLADOS DE Fusarium spp. CAUSADORES DE PODRIDÃO-DE-RAÍZES DA ERVA-MATE

Abstract: ResumoUma das principais doenças da erva-mate (Ilex paraguariensis A. St.-Hil.), em viveiro e, principalmente, a campo, é a podridão-de-raízes, causada por Fusarium spp. O controle da doença é dependente da diagnose correta de seu agente etiológico e as características moleculares e morfológicas permitem diagnosticar o patógeno. Assim, o objetivo deste trabalho foi determinar as características morfológicas e moleculares de seis isolados de Fusarium spp. oriundos de plantios de erva-mate doentes. Para isso, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
2
0
3
Order By: Relevance
“…The morphological characteristics observed in this work resemble those described by Poletto et al (2010) and Poletto et al (2012) for Fusarium oxysporum that causes root rot in yerba mate (Ilex paraguariensis). The clear violet coloration of the colonies was also verified by Su & Fu (2013) in isolates of root rot F. oxysporum in Pulsatilla koreana.…”
Section: Morphological Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…The morphological characteristics observed in this work resemble those described by Poletto et al (2010) and Poletto et al (2012) for Fusarium oxysporum that causes root rot in yerba mate (Ilex paraguariensis). The clear violet coloration of the colonies was also verified by Su & Fu (2013) in isolates of root rot F. oxysporum in Pulsatilla koreana.…”
Section: Morphological Characterizationsupporting
confidence: 88%
“…The results of this study corroborate those found by Cao et al (2013) who observed that Chinese licorice seedlings (Glycyrrhiza uralensis) with root rot caused by F. oxysporum and F. solani showed an abnormality in the aerial part such as yellowing and subsequent falling of the leaves. The same occurred in yerba mate when the pathogens F. oxysporum and F. solani caused root rot in plants in the nursery and in the field; in addition to necrotic roots, yellowing, necrosis, and leaf drop occurred (Poletto et al, 2012). In the beetroot (Beta vulgaris) the pathogen F. oxysporum, besides causing root necrosis, caused root vascular discoloration and foliar symptoms, including yellowing and inter-nerval wilting (Hanson & Jacobsen, 2006).…”
Section: Pathogenicity Testmentioning
confidence: 90%
“…Fusarium é um gênero de fungos saprofíticos que são facilmente encontrados no solo (LESLIE & SUMMERELL, 2008). Esses fungos são associados a diversas contaminação de plantas, inclusive em plantas com valor econômico (POLETTO et al 2012, LIMA & DUARTE. 2002MACIEL, 2012).…”
Section: Resultsunclassified
“…St.-Hil. ), two species (F. solani and F. oxysporum) were observed, which were potentially pathogenic, and the main symptom observed was root rot (Poletto et al, 2012).…”
Section: Pathogenicity Testmentioning
confidence: 99%